TAJIKISTAN BETWEEN RUSSIA,THE WEST, AND THE EAST - MULLOJANOV, Parviz (CENTRAL ASIA AND THE CAUCASUS, 2004)
Throughout mankind’s long political history, small states have been inevitably forced to join, in one way or another, the spheres of in-fluence of one or several powers, otherwise known as “centers of power.” Some obvious disadvantages of this, the resulting provincial status, limited (or no) access to the outside world, decline in the use of the mother tongue and ethnic culture because of forced or natural assimilation, economic dependence, and so on, went hand in hand with the obvious advantage of sustainable and peaceful development. On the contrary, changing one “traditional "patron for another was usually accompanied by social and political upheavals which sometimes deprived the small country of any future. Those which attempted to strike a balance among the interests of several power centers were rarely successful—they merely postponed for a while the need to join the sphere of influence of the geopolitical victor.